Metagenomic Analysis Revealed Differences in Composition and Function Between Liquid-Associated and Solid-Associated Microorganisms of Sheep Rumen - Su, Manchun; Hao, Ziyun; Shi, Huibin; Li, Taotao; Wang, Huihui; Li, Qiao; Zhang, Yong; Ma, Youji (Frontiers in Microbiology, 2022)
The rumen microbiota plays a key role in the utilization of plant material, yet little is known about the key taxa and potential gene functions involved in the digestion process. Understanding the differences in the composition and function of ruminal microbiota in the liquid-associated (LA) and solid-associated (SA) systems is needed to further study and regulate rumen function. In this study, nine Hu-sheep fed a high concentrate diet were selected to investigate the differences in the composition and function of these two systems using metagenome sequencing, and the potential of both systems to degrade carbohydrates was evaluated with emphasis. We found that the composition of dominant species was similar between these two systems, but the relative abundance of SA microorganisms was higher than that of LA microorganisms in all taxa. The concentration of fiber-degrading bacteria was higher and starch-utilizing bacteria was lower in the SA versus LA system. Furthermore, SA microorganisms dominate in cellulose degradation, while LA microorganisms are more important in starch utilization based on KEGG-KO gene and CAZymes gene. In general, SA microorganisms are more abundant and important in metabolic functions than LA, such as global and overview maps, carbohydrate and amino acid metabolism. Our results revealed that the differences in the composition of species and metabolic functions between two systems microorganisms, which were important for understanding the relationship between rumen microbiota and functions, and could provide guidance for rumen sampling.